Organosilicon films deposited in low-pressure plasma from hexamethyldisiloxane — A review - de Freitas, Amanda S.M.; Maciel, Cristiane C. [UNESP]; Rodrigues, Jéssica S.; Ribeiro, Rafael P. [UNESP]; Delgado-Silva, Adriana O.; Rangel, Elidiane C. [UNESP] (Elsevier, 2021)
We present a review of low-pressure plasma-enhanced chemical vapor deposition (PECVD) with the hexamethyldisiloxane (HMDSO) precursor for production of organosilicon thin films. This topic has been the subject of numerous studies in recent years, and there is a need for a focused review. Low-pressure plasma represents a simple, cost-effective, and environmentally friendly methodology for depositing films. The use of HMDSO as a precursor is justified by the advantages of this compound as the source of high vapor pressure, the high deposition rates that may be imposed, as well as the possibilities of adjustment of the properties and of the chemical nature of the final coating. Thus, the association of PECVD in a low-pressure system with HMDSO leads to a series of favorable implications for the development of new materials and technologies. In this work, before discussing the properties and application possibilities of organosilicon films, we present the concepts involved with low-pressure plasma deposition kinetics. The strict correlation between the plasma excitation parameters (such as pressure, power, and time) with the deposition kinetics and the final film properties is discussed. After that discussion, some specific properties of organosilicon films are presented and illustrated with results reported in the literature. The films produced in the consulted works modified the surface properties of polymeric, metallic, fabric, and membrane substrates. The modifications were evaluated in terms of surface-thermodynamic, anticorrosive, optical, mechanical, and barrier properties, among others. The possible applications for the treated materials in biomedical, energy, optics, sensoring, and separation systems, among others, are presented.
Keywords: Deposition kinetics; Functional films; HMDSO; Organosilicon; PECVD